Mobility Practices and Gender Contracts: Changes in Gender Relations in Coastal Areas of Norway - Gerrard, Siri (Umeå University, 2017)
Source at https://journals.ub.umu.se/njolas/article/view/11 This article addresses the relationship between gender contracts and mobility practices in fishery communities of Norway’s High North, mainly Skarsvåg, Finnmark. By combining perspectives from gender research, anthropology and geography, the aim of this article is to contribute to a greater understanding of the interrelations between structural, material, and cultural changes in the context of a smallscale coastal fishing environment. My main question is whether changes in mobility practices, related to restructuring of the fisheries by means of a quota-system, Norway’s agreement with the European Union (EEA) and other changes in the Norwegian context, have had impacts on gender contracts and in what way. Emphasis lies on the period after World War II and until today. The data collection are based on a lifelong engagement on gender questions in fishery villages, reading newspapers and using registers as well as interviews and participant observation through several research projects.